Imaging Changes in Lymphoid Organs In Vivo after Brain Ischemia with Three-Dimensional Fluorescence Molecular Tomography in Transgenic Mice Expressing Green Fluorescent Protein in T Lymphocytes - Abraham Martin; Juan Aguirre; Ana Sarasa-Renedo; Debbie Tsoukatou; Anikitos Garofalakis; Heiko Meyer; Clio Mamalaki; Jorge Ripoll; Anna M. Planas (Molecular Imaging)
Stroke induces a strong inflammatory reaction in the brain and depresses the immune system. We sought to assess longitudinal changes in T-cell numbers in the lymphoid organs of living mice after brain ischemia. Middle cerebral artery occlusion was carried out in transgenic mice expressing green fluorescent protein (GFP + ) in the T-cell population under the control of the hCD2 locus control region. Imaging was performed by three-dimensional fluorescence molecular tomography (FMT) before and at several time points after ischemia or sham operation and in controls. At day 7, GFP + cell content in lymphoid organs was measured postmortem by flow cytometry. GFP + cell numbers and in vivo FMT signal intensity were reduced at day 7 after ischemia and, to a lesser extent, after sham operation. Linear regression analysis demonstrated that postmortem GFP + cell numbers and corresponding in vivo FMT data were significantly correlated in the thymus ( r 2 = .65, p < .0001) and lymph nodes ( r 2 = .67, p < .0001). These relationships allowed inferring the number of GFP + T cells from in vivo FMT data. The results show the time course reduction of T-cell content in the lymphoid organs of living mice, providing in vivo evidence of lymphoid organ atrophy after stroke and, to a lesser extent, after head surgery with craniectomy and dura mater opening in sham-operated mice.